Effect of mulberry leaf (Folium Mori) on insulin resistance via IRS-1/PI3K/Glut-4 signalling pathway in type 2 diabetes mellitus rats. (1st November 2016) - Cai, Shengyu; Sun, Wen; Fan, Yixin; Guo, Xuan; Xu, Guangyuan; Xu, Tunhai; Hou, Yi; Zhao, Baosheng; Feng, Xingzhong; Liu, Tonghua
Abstract: Context: Folium Mori, the leaf of Morus alba L. (Moraceae), has been used in traditional Chinese medicine (TCM) for treating diabetes. However, it is unclear which components in the mulberry leaf are effective for the treatment of type 2 diabetes mellitus (T2DM). Objective: To investigate the flavonoids and polyphenols in mulberry leaves and their antihyperglycemic and antihyperlipidemic effects in T2DM rats. Materials and methods: Male Sprague-Dawley rats were divided into five groups: normal control (NC), diabetic control (DBC), diabetic group with 0.3 mg/kg b.w./day rosiglitazone (RSG), diabetic group with 7 g/kg b.w./day TCM formula and diabetic group with 2 g/kg b.w./day Folium Mori extract (FME). After 4 weeks, the rats were sacrificed; biochemical parameters, gene and protein expression were measured. Results: The FBG level was significantly lower in the FME group than in the DBC group ( p < 0.05). In oral glucose tolerance test, the AUC was significantly lower in the FME group ( p < 0.05). The HOMA-IR level was significantly decreased in the FME group ( p < 0.05). FME decreased the total cholesterol (TC), triglyceride (TG) and low density lipoprotein (LDL) levels ( p < 0.05). FME increased the mRNA and protein expression of IRS-1, PI3K p85α and Glut-4 increased significantly ( p < 0.05). Histological analysis revealed amelioration of lipid accumulation following FME treatment. Additionally, immunohistochemical analysis displayed stronger staining of Glut-4 in the FME group compared to the DBC group. Discussion and conclusion: FME could decrease the body weight, blood glucose, TG, TC and LDL levels, and improve insulin resistance. FME possessed significant antihyperglycemic and antihyperlipidemic activities via the IRS-1/PI3K/Glut-4 signalling pathway.